The Roles of Families in Combating Drugs Uses, Violence and Terrorism - Nasution, Khoiruddin (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2021)
This paper aims to strengthen the opinion or the concept suggesting that family roles are significant in the attempt to overcome drug uses, violence and terrorism in Indonesia. This is a qualitative research, in which sources of data were literary works, such as academic books and articles. The article refers to Berger’s theory of social construction during the first stage in the process of externalization out of three stages: externalization, objectification and internalization, which lead to transformation of social actions, which then shape people’s habits. Meanwhile, in the effort to control Social Actions or control people’s habits, the article refers to preventive and repressive efforts, while in terms of the process of social control; the article refers to persuasive, coercive and curative efforts. Our findings suggest that three main social problems: first, drug uses, violence against children, wives, and husbands and terrorism are still main social problems in Indonesia, which require serious, substantial and sustainable efforts to find effective solutions.However, population growth also needs attention even though it is not as vital as others mentioned earlier; second, there are several important reasons and/or factors that problem of drugs, violence and terrorism persist in Indonesia, one of which is the failure of the family to take important role in guiding its members;third, based on our reviews of literature, we conclude that to maximize roles of family, marriage couples should be knowledgeable and competent in keeping their family runs well. For that reason, it is paramount important for marriage couples to educate themselves regarding their roles and responsibilities within the family life. This can be done through taking the pre-marriage courses for those who are about to get married. In fact, marriage couples should persistently educate themselves through many means and channels.